Human condition [videorecording (DVD)] - Kobayashi, Masaki, 1916-1996; Kobayashi, Masaki, 1916-1996; Nakadai, Tatsuya, 1932-; Aratama, Michiyo; Sada, Keiji, 1926-1964; Gomikawa, Junpei, 1916-1995 (Criterion collection, 2009)
Tells of the journey of the well-intentioned yet naive Kaji from labor camp supervisor to Imperial Army soldier to Soviet POW. Constantly trying to rise above a corrupt system, Kaji time and again finds his morals an impediment rather than an advantage.